2016
DOI: 10.1063/1.4942221
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dielectric properties of Na0.5Bi0.5TiO3-CaTiO3 solid solutions

Abstract: Despite wide studies of Na0.5Bi0.5TiO3, structure of this material and its connection with the observed physical properties still raise numerous questions due to mutually contradicting results obtained. Here, structure and dielectric properties of poled and unpoled Na0.5Bi0.5TiO3-CaTiO3 solid solutions are studied, projecting the obtained concentration dependence of structure and dielectric properties on pure Na0.5Bi0.5TiO3 as the end member of this material group. X-ray diffraction patterns for Na0.5Bi0.5TiO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Moreover, Du et al [49] demonstrated that this system is susceptible to orthorhombic distortion for x ≥ 0.14 and the MPB was found to lie around 0.08 ≤ x < 0.14. On the contrary, Birks et al [50] reported the structural properties of poled and unpoled conditions of (1-x)NBT-xCT assuming the coexistence of rhombohedral and orthorhombic phases. Despite the various studies of NBT-CT system, the structure of these materials and its link to the obtained physical properties are still not understood and under investigation due to mutual contradicting results.…”
mentioning
confidence: 99%
“…Moreover, Du et al [49] demonstrated that this system is susceptible to orthorhombic distortion for x ≥ 0.14 and the MPB was found to lie around 0.08 ≤ x < 0.14. On the contrary, Birks et al [50] reported the structural properties of poled and unpoled conditions of (1-x)NBT-xCT assuming the coexistence of rhombohedral and orthorhombic phases. Despite the various studies of NBT-CT system, the structure of these materials and its link to the obtained physical properties are still not understood and under investigation due to mutual contradicting results.…”
mentioning
confidence: 99%
“…Obviously, the different behavior indicates different states of the poled and the depoled sample even in the temperature range, where the poled state is destroyed. A different behavior was observed also for the temperature and frequency dependences of dielectric permittivity [37].…”
Section: Resultsmentioning
confidence: 89%
“…For the total calculated T(T), this temperature is shifted in the direction of high temperatures due to contribution of d 2 /dT ( Figure 7). Since nature of the electric field-induced polarization is rather complicated in the temperature range between T d and T m , where relaxor properties continuously diminish and diffused phase transition to orthorhombic phase is approached upon increasing of temperature [37], it is hard to comment such coincidence at the moment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations